Analyzing the detrimental effects of female chronic hepatitis B virus DNA on ovarian reserve function and results of in vitro fertilization - Liu Liu; Hua Liang; Jing Yang; Fujin Shen; Wei Li (IMR Press, 2022)
Background: To evaluate both the impact of hepatitis B virus (HBV)-DNA copies in women with HBV infection on the ovarian reserve function and outcomes of in vitro fertilization (IVF). Methods: We conducted a retrospective study on a total of 9927 couples undergoing their first IVF cycle. After filtering, 1570 couples (546 HBV-seropositive women and 1024 HBV-seronegative women whose partners were HBV-seronegative) failed to meet inclusion criteria. According to the HBV-DNA titers in serum, the HBV-seropositive group was divided into three groups: DNA-high copy group (n = 139), DNA-low copy group (n = 241), and DNA-negative group (n = 166). All patients underwent controlled ovarian hyperstimulation using the long downregulation protocol followed by IVF. Results: Compared with the HBV-negative group, HBV-positive women with high DNA copy exhibited lower antral follicle count (AFC) (11.9 ± 4.3 vs 13.3 ± 3.2), lower number of oocyte retrieved (9.2 ± 5.7 vs 13.1 ± 6.1), larger proportion of AFC <8 (7.9% vs 3.1%) and anti-mullerian hormone (AMH) <2 μg/L (8.6% vs 4.3%). Both high-DNA copy and low-DNA copy groups exhibited a lower fertilization rate (70.9% and 72.5% vs 75.1%), lower high-grade embryo rate (51.5% and 53.8% vs 56.9%), lower implantation rate (31.3% and 32.7% vs 38.5%), lower clinical pregnancy rate (40.3% and 42.3% vs 49.6% per cycle with OR; 45.5% and 48.8% vs 56.8% per cycle with ET) than the HBV-negative group. Moreover, a higher early abortion rate (19.6% and 15.7% vs 7.1%) was observed in the above two groups. Conclusion: HBV-DNA may have a negative effect on women's ovarian reserve function which in turn results in poor fertilization rate, clinical pregnancy rate and high early abortion rate in IVF treatment.